Activity of glutathione S‐transferase and esterase enzymes in Helicoverpa armigera (Hübner) after exposure to entomopathogenic fungi. Issue 4 (23rd March 2018) - Bilal, Muhammad; Freed, Shoaib; Muhammad, Saleh; Ashraf, Muhammad Zubair; Khan, Muhammad Bismillah
Abstract: Helicoverpa armigera, a polyphagous insect of crops and vegetables, is acquiring resistance against many commercial insecticides. The present study shows variations in the activity of two detoxification enzymes, namely esterase and glutathione S‐transferase (GST), in H. armigera after exposure to different isolates of entomopathogenic fungi. After treatment of larvae with the different isolates (Day 0), samples were collected on three days (Days 3, 5 and 7) for enzyme analysis. High GST activity was found in samples of hemolymph, intestine and fat bodies of H. armigera following treatment with Beauveria bassiana (isolate Bb‐08), Metarhizium anisopliae (isolates Ma‐11.1 and Ma‐4.1), and Isaria fumosorosea (isolates If‐02 and If‐2.3). High esterase activity was recorded in samples of the intestine and fat bodies on various days after treatment, whereas increased esterase activity in hemolymph was noted only in samples from Day 5 after treatment with M. anisopliae (Ma‐4.1). The detection of high GST and esterase activity demonstrates the possibility of the development of resistance against these microbial control agents in H. armigera.